Diffusion MRI Findings in Encephalopathy Induced by Immunosuppressive Therapy after Liver Transplantation - Emanuele Tinelli; Nicoletta Locuratolo; Alberto Pierallini; Massimo Rossi; Francesco Fattapposta (Case Reports in Medicine)
Neurological complications are common after liver transplantation, as they affect up to one-third of the transplanted patients and are associated with significant morbidity. The introduction of calcineurin inhibitors, cyclosporine A and tacrolimus, in immunosuppressive regimens significantly improved the outcome of solid-organ transplantation even though immunosuppression-associated neurotoxicity remains a significant complication, particularly occurring in about 25% of cases after liver transplantation. The immunosuppressant cyclosporine A and tacrolimus have been associated with the occurrence of major neurological complications, diffuse encephalopathy being the most common. The biochemical and pathogenetic basis of calcineurin inhibitors-induced neurotoxicity are still unclear although several mechanisms have been suggested. Early recognition of symptoms could help reduce neurotoxic event. The aim of the study was to evaluate cerebral changes through MRI, in particular with diffusion-weighted images (DWI) and apparent diffusion coefficient (ADC) maps, in two patients undergoing liver transplantation after immunosuppressive therapy. We describe two patients in which clinical pictures, presenting as a severe neurological condition, early after orthotopic liver transplantation during immunosuppression therapy, showed a different evolution in keeping with evidence of focal-multifocal lesions at DWI and ADC maps. At clinical onset, DWI showed hyperintensity of the temporo-parieto-occipital cortex with normal ADC values in the patient with following good clinical recovery and decreased values in the other one; in the latter case, MRI abnormalities were still present after ten days, until the patient’s exitus. The changes in DWI with normal ADC may be linked to brain edema with a predominant vasogenic component and therefore reversible, while the reduction in ADC is due to cytotoxic edema and linked to more severe, nonreversible, clinical picture. Brain MRI and particularly DWI and ADC maps provide not only a good and early representation of neurological complications during immunosuppressant therapy but can also provide a useful prognostic tool on clinical outcome of the patient.